Peran Modal Sosial dalam Pengembangan Desa Wisata Serangan Denpasar Bali - I Gede Putra Nugraha (Media Wisata, 2021)
Serangan Village as a potential area is a representation of Denpasar City Government's policy on environmental conservation, history and cultural values, the interests of the world of education, and the interests of cultural tourism full of attractions. The purpose of this study was to identify the role of social capital in the development of sustainable tourism in Serangan Village and to analyze the influence of the role of government, community participation, and social capital on the quality of destinations and sustainable tourism development in Serangan Village. The results of this study are the role of social capital norms in Serangan Village has an important role in tourism development in Serangan Village, where norms in traditional villages in Serangan Village are still very strong.